2017
DOI: 10.1038/s41598-017-02203-3
|View full text |Cite
|
Sign up to set email alerts
|

Adamdec1, Ednrb and Ptgs1/Cox1, inflammation genes upregulated in the intestinal mucosa of obese rats, are downregulated by three probiotic strains

Abstract: We have previously reported that administration of Lactobacillus paracasei CNCM I-4034, Bifidobacterium breve CNCM I-4035 and Lactobacillus rhamnosus CNCM I-4036 to obese Zucker-Leprfa/fa rats attenuates liver steatosis and exerts anti-inflammatory effects. The goal of the present work was to investigate the modulation of gene expression in intestinal mucosa samples of obese Zucker-Leprfa/fa rats fed the probiotic strains using a DNA microarray and postgenomic techniques. We also measured secretory IgA content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…It has been demonstrated that probiotics can affect the structure of gut microbiota and the interaction with the microbial community and the host health through different mechanisms [12,[193][194][195]. These effects are mediated by the direct or indirect action of probiotics and can involve the modulation of the immune system or that of remote organs like the brain and liver due to the production of metabolites finally localized in these organs [193,[196][197][198][199].…”
Section: Probiotic Administration Microbiota Bile Acids and Cardiovmentioning
confidence: 99%
“…It has been demonstrated that probiotics can affect the structure of gut microbiota and the interaction with the microbial community and the host health through different mechanisms [12,[193][194][195]. These effects are mediated by the direct or indirect action of probiotics and can involve the modulation of the immune system or that of remote organs like the brain and liver due to the production of metabolites finally localized in these organs [193,[196][197][198][199].…”
Section: Probiotic Administration Microbiota Bile Acids and Cardiovmentioning
confidence: 99%
“…Ohtsuka et al 12 administered Bifidobacterium breve M-16V to rat pups during the newborn period and found a lower expression of various inflammation-related genes in the colon. This descriptor is based on the data of our recently published work 13 , whose goal was to investigate whether these bacterial strains may modulate the gene expression of the intestinal mucosa. For this purpose and with the help of DNA microarray technology, we began by studying the modulation of a great number of genes in intestinal mucosa samples from obese Zucker rats.…”
Section: Background and Summarymentioning
confidence: 99%
“…Alteration to the gut microbiome through the administration of beneficial microbes, typically referred to as probiotics, is an active area of investigation [ 15 , 20 , 21 , 22 ]. Probiotics are defined as “live microorganisms that confer a health benefit to the host when administered in adequate amounts, although dead bacteria and bacterial molecular components may also exhibit probiotic properties” [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alteration to the gut microbiome through the administration of beneficial microbes, typically referred to as probiotics, is an active area of investigation [ 15 , 20 , 21 , 22 ]. Probiotics are defined as “live microorganisms that confer a health benefit to the host when administered in adequate amounts, although dead bacteria and bacterial molecular components may also exhibit probiotic properties” [ 22 ]. Recent reviews and meta-analyses have suggested an effect of probiotics in the treatment and prevention of gastrointestinal and upper respiratory infections in children [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation